=
=
=
=
=
=
=
Made new thread because I got new expression to solve. I have tried to get answer by myself, but ended with different result.
Expression:
Answer:
I have done this:
Here (x-2) should cancel each other out which leaves:
Pretty nice, when I made x=1 and solved my gigantic simplification it gave same result as text book simplification: 1/15
My creation blows, where I have done mistakes? How this needs to be done?
Thank you very much, now I can learn from your simplification. Bringing 2x in front of expression is new for me.
EDIT:
When you do this:
Will it only affect denominator and its argument places? When you change term sign then arguments in denominator get swapped? Will numerator stay unchanged by that move? Can I read somewhere about that operation?
Two different things are going on here. First, you have this subtracting property: a - b = -(b - a). Swapping the order of subtraction requires you to put a negative outside. So what was done in the above was that
.
Next, you have a fraction where the denominator is negative. When dealing with negatives, remember that the following fractions are equivalent:
. The negative sign in our problem was in the denominator, and can be moved to in front of the fraction:
.
01